2019
DOI: 10.1186/s12879-019-4102-4
|View full text |Cite
|
Sign up to set email alerts
|

Causative agents and outcome of spontaneous bacterial peritonitis in cirrhotic patients: community-acquired versus nosocomial infections

Abstract: Background Spontaneous bacterial peritonitis (SBP) is a serious complication and common cause of death in patients with liver cirrhosis. This study was conducted to compare the microbiological characteristics, drug resistance, and treatment outcomes for nosocomial SBP and community-acquired SBP. Methods A retrospective study was performed on 334 patients with culture-positive SBP at Beijing Youan Hospital, China, between January 2012 and December 2016. The medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
7
36
0
Order By: Relevance
“…Kirplani et al (Pakistan) [28] found cases of Escherichia coli resistant to Ceftriaxone (32%) and Sulfamethoxazole/trimethoprim (10.9%). Another study by Ding et al showed similar results [14]. The frequent and inadequate use of cephalosporins and sulfamethoxazole/trimethoprim in Madagascar may explain these facts [29].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Kirplani et al (Pakistan) [28] found cases of Escherichia coli resistant to Ceftriaxone (32%) and Sulfamethoxazole/trimethoprim (10.9%). Another study by Ding et al showed similar results [14]. The frequent and inadequate use of cephalosporins and sulfamethoxazole/trimethoprim in Madagascar may explain these facts [29].…”
Section: Discussionmentioning
confidence: 77%
“…Bacterial translocation is increased in gastrointestinal bleeding in patients with cirrhosis. Gastrointestinal bleeding was a risk factor to SBP [12][13][14][15]. Primary prevention of SBP with prophylactic antimicrobials should be initiated in gastrointestinal bleeding in patients with cirrhosis [2,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study, Ding et al [25] analyzed the etiology of 334 Chinese patients with SBP from 2012 to 2016 and arrived at a similar conclusion. A total of 334 pathogenic bacteria were isolated, including 178 gram-negative bacteria and 138 gram-positive bacteria.…”
Section: Epidemiologymentioning
confidence: 76%
“…Spontaneous bacterial peritonitis occurs with a prevalence of 10-25% in cirrhotic patients with ascites [54]. It can be community acquired, health care associated or nosocomial.…”
Section: Spontaneous Bacterial Peritonitis (Sbp)mentioning
confidence: 99%
“…Nosocomial SBP has a poorer outcome than community acquired pneumonia (24.6% vs. 36.8%; P = 0.016). The independent predictors for 30-day mortality are nosocomial infection, Child-Pugh classification, hepatocellular carcinoma, renal failure and hepatic encephalopathy [54].…”
Section: Spontaneous Bacterial Peritonitis (Sbp)mentioning
confidence: 99%